Aqueous zinc ion battery and electrolyte and preparation method thereof

By using the coupling effect of carbon quantum dots and specific solvents in the electrolyte of zinc ion battery, the problems of dendrites and side reactions are solved, the deposition and dissolution reversibility and cycle stability of zinc negative electrodes are improved, and the performance of efficient and safe zinc ion battery is achieved.

CN119542568AActive Publication Date: 2025-02-28DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311117218.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-31
Publication Date
2025-02-28
Estimated Expiration
2043-08-31

AI Technical Summary

Technical Problem

Water-based zinc ion batteries are prone to dendrite and side reactions during use, resulting in electrode failure and low cycle life, affecting the safety and electrochemical performance of the battery.

Method used

By adding carbon quantum dots to the electrolyte to form a coupling effect with a specific solvent, the deposition behavior of zinc is regulated, the formation of dendrites and by-products is inhibited, thereby improving the deposition and dissolution reversibility of zinc negative electrodes.

Benefits of technology

The preferred deposition of zinc negative electrode in the electrolyte along the (002) crystal surface, zinc-free dendrites and by-products are achieved, which improves the cycle stability and deposition/dissolution performance of the battery, and is simple and cost-effective.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004425592650000011
    Figure HDA0004425592650000011
  • Figure HDA0004425592650000021
    Figure HDA0004425592650000021
  • Figure HDA0004425592650000031
    Figure HDA0004425592650000031
Patent Text Reader

Abstract

The invention discloses an aqueous zinc ion battery and an electrolyte and a preparation method thereof. The carbon quantum dot additive in the electrolyte is prepared by a solvent synthesis method, an electrolyte solvent is a mixed solution of water and an organic solvent coupled with carbon quantum dots, a solute is zinc salt (ZnXa), and the organic solvent is one or more of methanol, ethanol, isopropanol, acetone and dimethylformamide; x is one or more of Cl <->, SO4 < 2->, NO3 <->, CH3COO <->, CF3SO3 <-> and ClO4 <->. And the zinc negative electrode comprises a zinc sheet, a zinc foil, zinc powder, a zinc net, porous zinc or zinc alloy. A zinc negative electrode working under the electrolyte shows excellent deposition and dissolution reversibility, and a zinc sheet after circulation shows the characteristics of compact deposition and no dendritic crystals and byproducts. The method is simple and low in cost, and the cycling stability of the zinc negative electrode in the water-based zinc ion battery can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a negative electrode protection method for improving the reversibility of zinc dissolution and deposition in a zinc ion battery through coupling regulation of an additive and an electrolyte, and belongs to the field of electrochemistry. Background Art

[0002] Against the backdrop of limited fossil fuel reserves and rising carbon dioxide emissions leading to global warming, the country has formulated "carbon peak" and "carbon neutrality" and other "dual carbon" indicators, and has increasingly paid attention to the promotion of renewable clean energy. However, renewable energy (such as solar and wind energy) needs to be equipped with high-safety, low-cost, and long-life energy storage technology to ensure the smooth output of energy due to its intermittent, volatile, random, and regional dependence. Compared with traditional mechanical energy storage, electromagnetic energy storage, thermal energy storage, and chemical energy storage, electrochemical energy storage (i.e., various secondary battery energy storage) is considered to play an important role in the future energy storage market due to its advantages such as flexible configuration, rapid response, and short construction period. At present, lithium-ion batteries dominate electrochemical energy storage (about 88%). However, the cost of lithium is high (US$19.2 / kg), and lithium-ion batteries use organic electrolytes, which have serious safety hazards. Once leaked or overheated, they are prone to fire and explosion. Therefore, there is an urgent need to develop low-cost and high-safety electrochemical energy storage technology.

[0003] my country has rich reserves of zinc metal (the world's first), which has the advantages of low cost (US$2.4 / kg), non-toxicity, and high theoretical capacity (5851 mAh / mL; 820 mAh / g). The redox potential of zinc is relatively low (-0.76 volts relative to the standard hydrogen electrode), which allows zinc-ion batteries to directly use aqueous electrolytes. Compared with organic electrolytes, the ionic conductivity of aqueous electrolytes is about two orders of magnitude higher (about 1000 millisiemens / cm vs. about 1-10 millisiemens / cm), so aqueous zinc-ion batteries can achieve rapid charging and discharging. In addition, thanks to the relatively stable chemical and physical properties of zinc metal, aqueous zinc-ion batteries have no risk of explosion or fire, and their high safety makes them have great potential in portable devices, electric vehicles, and large-scale energy storage.

[0004] However, aqueous zinc-ion batteries currently face key problems such as dendrites and side reactions, which can easily lead to electrode failure or low cycle life. Zinc dendrites can easily pierce the diaphragm, causing the battery to short-circuit, and can also cause uneven electrode thickness, causing electrode deformation; side reactions (including water corrosion, hydrogen evolution reaction, etc.) not only reduce zinc utilization and battery coulomb efficiency, but the production of hydrogen will also affect the safety and electrochemical performance of the battery. Therefore, effectively inhibiting the occurrence of zinc dendrites and side reactions is a difficult problem that must be solved in the development of zinc-ion batteries. Summary of the invention

[0005] The purpose of the present invention is to avoid zinc dendrites and side reactions, thereby improving the cycle stability of the negative electrode of a zinc ion battery. The present invention provides a zinc negative electrode protection method that forms a coupling effect between carbon quantum dots and a specific solvent to inhibit dendrites and byproducts and improve the reversibility of zinc negative electrode dissolution and deposition in a zinc ion battery. That is, by adjusting the concentration of carbon quantum dots in the electrolyte system, the proportion and type of the coupled organic solvent, the deposition behavior of zinc is guided at the electrode / solution interface on the zinc negative electrode side of the zinc ion battery, so that the zinc negative electrode achieves reversible deposition and dissolution. The battery cycle performance results show that the zinc negative electrode preferentially deposits along the (002) crystal plane in the regulated electrolyte, without the generation of zinc dendrites and byproducts, and has efficient and reversible deposition / dissolution performance; the method is simple and low cost.

[0006] The present invention uses zinc-based materials as zinc negative electrode active materials, carbon quantum dots as electrolyte additives, the solvent of the electrolyte is water or a mixture of water and an organic solvent, and the solute is a zinc salt (ZnX a ), the carbon quantum dots of the present invention form a coupling effect with a specific solvent to suppress dendrites and by-products.

[0007] The invention provides an electrolyte containing carbon quantum dots for protecting a zinc negative electrode in a zinc ion battery. The electrolyte comprises hydrophobic carbon quantum dots as electrolyte additives, a mixed solution of solvent water and an organic solvent, and a solute of zinc salt. The organic solvent is one or more of methanol, ethanol, isopropanol, acetone and dimethylformamide.

[0008] Furthermore, in the above technical solution, the volume ratio of the organic solvent to water is 0 to 1 and is not zero, that is, greater than 0 and less than or equal to 1;

[0009] Furthermore, in the above technical solution, the method for preparing the hydrophobic carbon quantum dots comprises the following steps:

[0010] 1) Using a small molecule organic solvent A, wherein A is one or more of methanol, ethanol, acetic acid, acetonitrile, acetone, butanone, ethylene glycol, formaldehyde, and acetaldehyde;

[0011] 2) Add the strong base powder B(OH) a , where B is one or more of Li, Na, Ka, Be, Mg, Ca, Sr, a = 1 to 2; small molecule organic solvent and strong base powder B (OH) a The dosage ratio is 10-100 mL: 1-40 g;

[0012] 3) stirring the solid-liquid mixture obtained in step 2) at a speed of 100 to 1500 rpm for 10 to 200 minutes and allowing it to stand for 1 to 50 days;

[0013] 4) neutralizing the product obtained in step 3) to pH = 7 using 0.1-10M hydrochloric acid or sulfuric acid;

[0014] 5) separating the carbon quantum dot-rich phase from the product obtained in step 4) and washing it with deionized water for 2 to 20 times;

[0015] 6) The product obtained in step 5) is dried under vacuum at 60-200° C. for 12-48 hours.

[0016] Furthermore, in the above technical solution, the solute zinc salt has the structural formula ZnX a , where X = Cl - 、SO4 2- 、NO3 - 、CH3COO - CF3SO3 - 、ClO4 - One or more of, a = 1 to 2; the zinc salt ZnX a The concentration is 0.1~5M.

[0017] The present invention provides a method for preparing the above-mentioned electrolyte, comprising the following steps:

[0018] (1) The carbon quantum dot powder is dissolved in a certain amount of organic solvent, wherein the organic solvent is one or more of methanol, ethanol, benzyl alcohol, phenol, propanol, benzene, isopropanol, acetonitrile, propionitrile, isopropionitrile, formaldehyde, acetaldehyde, propionaldehyde, acetone, butanone, formic acid, acetic acid, dimethylformamide, and dimethylformamide, and the concentration of the carbon quantum dots is 0 to 50 mg / mL and cannot be 0;

[0019] (2) Add a certain amount of zinc salt ZnX a Dissolved in aqueous solution, where X = Cl - 、SO4 2- 、NO3 - 、CH3COO - CF3SO3 - 、ClO4 - One or more of, a = 1 to 2; the zinc salt ZnX a Concentration is 0.1~6M;

[0020] (3) adding the organic dispersion of carbon quantum dots in step (1) to the electrolyte in step (2), stirring until a transparent and clear liquid is obtained, and ultrasonicating for 10 to 500 minutes;

[0021] (4) The liquid obtained in step (3) is allowed to stand for 0 to 5 days and is not zero, and is filtered to obtain a clarified electrolyte.

[0022] The present invention provides a zinc ion battery, which is characterized by containing the above electrolyte and using zinc-based materials as zinc negative electrode active materials.

[0023] Furthermore, in the above technical solution, the zinc negative electrode is a zinc sheet, zinc foil, zinc powder, zinc mesh, porous zinc or zinc alloy.

[0024] The reversibility of zinc negative electrode deposition and dissolution in the electrolyte prepared by the present invention was evaluated using a zinc symmetric cell, and the process was as follows:

[0025] The two zinc negative electrodes are placed in the corresponding positions in the battery mold, and the separator is placed in the middle to isolate the electron transport and then the electrolyte is added. Then the button battery sealing machine is used to complete the packaging of the zinc negative electrode symmetrical battery. The packaged battery is connected to the electrochemical charge and discharge instrument and the current density is specified (0.1~20mA / cm 2 ) was used to conduct a cyclic stability test.

[0026] Beneficial results:

[0027] The size of the carbon quantum dots synthesized by the solvent in the present invention is less than 5nm (transmission electron microscopy image as shown in FIG. Figure 1 As shown in the figure), the electrolyte regulated by coupling carbon quantum dots with organic solvents can induce strong preferential growth of zinc on the (002) crystal plane (2θ=36°) during zinc deposition. The XRD test results show that the strongest peak of the zinc sheet after the cycle corresponds to the (002) crystal plane of zinc (the strongest XRD peak of the initial zinc (2θ=43°) corresponds to the (101) crystal plane), and there is no XRD peak of the by-product Zn4(OH)6SO4·xH2O (XRD results are shown in the figure). Figure 2 The surface morphology of zinc after 800 hours of cycling was observed by scanning electron microscope, showing that there were no zinc dendrites and byproducts on the zinc surface (the scanning electron microscope results are shown in Figure 1 The zinc symmetric battery exhibits excellent zinc deposition and dissolution reversibility, and the voltage-time curve is symmetrical, stable, and gentle; at 0.5 mA / cm 2 At a current density of , the cycle life can reach 1400h (the voltage-time curve of the battery cycle test is as follows Figure 3 shown).

[0028] The method provided by the invention has short time consumption, simple steps, low cost and good repeatability. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Transmission electron microscope photos of carbon quantum dots used in Examples 1-8

[0030] Figure 2 This is a scanning electron microscope photograph of the zinc surface of the battery in Example 1-8 after cycling.

[0031] Figure 3This is the X-ray diffraction (XRD) spectrum of the zinc foil after the battery cycle in Example 1.

[0032] Figure 4 The voltage-time curve of the battery cycle test in Example 1.

[0033] Figure 5 This is a scanning electron microscope photograph of the zinc surface after the battery in Comparative Example 1 was cycled.

[0034] Figure 6 This is the X-ray diffraction (XRD) spectrum of the zinc foil after the battery cycle in Comparative Example 1.

[0035] Figure 7 This is a scanning electron microscope photograph of the zinc surface after the battery in Comparative Example 3 was cycled.

[0036] Figure 8 This is the X-ray diffraction (XRD) spectrum of the zinc foil after the battery cycle in Comparative Example 3. DETAILED DESCRIPTION

[0037] The following examples will further illustrate the present invention, but are not intended to limit the invention.

[0038] Example 1

[0039] Synthesis of Carbon Quantum Dots:

[0040] 8g NaOH powder was added to 40mL acetone, magnetically stirred at 800rpm for 90min, and then sealed and allowed to stand for 5 days to obtain a black solid mixture. 1M hydrochloric acid was added to the mixture until pH = 7. The mixed solution was stratified, and the upper layer was the enriched phase of carbon quantum dots. After washing the enriched phase with deionized water 10 times, the enriched phase of carbon quantum dots was vacuum dried at 100℃ for 24h to obtain hydrophobic carbon quantum dot powder. Electrolyte configuration scheme:

[0041] Weigh 20 mg of synthesized carbon quantum dot powder and dissolve it in 2 mL of ethanol; weigh 11.5 g of ZnSO4·7H2O powder and dissolve it in 20 mL of deionized water. Add the ethanol dispersion of carbon quantum dots into the zinc sulfate solution and ultrasonicate for 1 h. After standing for 1 day, filter to obtain a clear electrolyte.

[0042] Battery assembly and results:

[0043] The zinc ion symmetric battery was assembled using commercial zinc foil and the electrolyte. The assembly steps were as follows: two zinc negative electrodes were placed in the corresponding positions in the battery mold, a separator was placed in the middle to isolate the electron transport, and then the electrolyte was added. Then, a button battery sealing machine was used to complete the packaging of the zinc negative electrode symmetric battery. The packaged battery was connected to an electrochemical charge and discharge instrument.

[0044] At 0.5 mA / cm2 Under the current density, the zinc surface after battery cycling is preferentially oriented to the (002) plane, and the zinc surface morphology is shown in Figure 2 ; The X-ray diffraction (XRD) spectrum of zinc after battery cycling is shown in Figure 3 ; The battery cycled stably for 1400h. The voltage-time curve of the battery cycle test is shown in Figure 4 .

[0045] Example 2

[0046] The synthesis steps of carbon quantum dots are shown in Example 1.

[0047] Electrolyte configuration scheme:

[0048] Weigh 1 mg of synthesized carbon quantum dot powder and dissolve it in 1 mL of isopropanol; weigh 5.4 g of ZnCl2 powder and dissolve it in 20 mL of deionized water. Add the isopropanol dispersion of carbon quantum dots into the zinc chloride solution and ultrasonicate for 1 h. After standing for 1 day, filter to obtain a clear electrolyte.

[0049] Battery assembly and results:

[0050] A zinc ion symmetrical battery was assembled using the zinc-aluminum alloy sheet and the electrolyte according to the steps of Example 1. 2 At a current density of , the zinc surface after battery cycling is preferentially oriented to the (002) plane, and the zinc surface morphology is shown in Figure 2 .

[0051] Example 3

[0052] The synthesis steps of carbon quantum dots are shown in Example 1.

[0053] Electrolyte configuration scheme:

[0054] 80 mg of synthesized carbon quantum dot powder was weighed and dissolved in 10 mL of dimethylformamide; 11.9 g of Zn(NO3)2·6H2O powder was weighed and dissolved in 20 mL of deionized water. The dimethylformamide dispersion of carbon quantum dots was added to the zinc nitrate solution and ultrasonicated for 1 h. After standing for 1 day, it was filtered to obtain a clear electrolyte.

[0055] Battery assembly and results:

[0056] The zinc powder supported by the stainless steel mesh and the electrolyte were used to assemble a zinc ion symmetrical cell according to the steps of Example 1. 2 At a current density of , the zinc surface after battery cycling is preferentially oriented to the (002) plane, and the zinc surface morphology is shown in Figure 2 .

[0057] Example 4

[0058] The synthesis steps of carbon quantum dots are shown in Example 1.

[0059] Electrolyte configuration scheme:

[0060] Weigh 90 mg of synthesized carbon quantum dot powder and dissolve it in 10 mL of ethanol; weigh 8.8 g of Zn(CH3COO)2·2H2O powder and dissolve it in 40 mL of deionized water. Add the ethanol dispersion of carbon quantum dots into the zinc acetate solution and ultrasonicate for 1 h. After standing for 1 day, filter to obtain a clear electrolyte.

[0061] Battery assembly and results:

[0062] The zinc powder supported by the stainless steel mesh and the electrolyte were used to assemble a zinc ion symmetrical cell according to the steps of Example 1. 2 At a current density of , the zinc surface after battery cycling is preferentially oriented to the (002) plane, and the zinc surface morphology is shown in Figure 2 .

[0063] Example 5

[0064] The synthesis steps of carbon quantum dots are shown in Example 1.

[0065] Electrolyte configuration scheme:

[0066] Weigh 250 mg of synthesized carbon quantum dot powder and dissolve it in 20 mL of methanol; weigh 23 g of ZnSO4·7H2O powder and dissolve it in 40 mL of deionized water. Add the methanol dispersion of carbon quantum dots into the zinc acetate solution and ultrasonicate for 1 h. After standing for 1 day, filter to obtain a clear electrolyte.

[0067] Battery assembly and results:

[0068] A zinc ion symmetrical battery was assembled using commercial zinc sheets and the electrolyte according to the steps of Example 1. 2 At a current density of , the zinc surface after battery cycling is preferentially oriented to the (002) plane, and the zinc surface morphology is shown in Figure 2 .

[0069] Example 6

[0070] The synthesis steps of carbon quantum dots are shown in Example 1.

[0071] Electrolyte configuration scheme:

[0072] Weigh 150 mg of synthesized carbon quantum dot powder and dissolve it in 15 mL of acetonitrile; weigh 11.5 g of ZnSO4·7H2O powder and dissolve it in 20 mL of deionized water. Add the acetonitrile dispersion of carbon quantum dots into the zinc sulfate solution and ultrasonicate for 1 h. After standing for 1 day, filter to obtain a clear electrolyte.

[0073] Battery assembly and results:

[0074] The zinc-aluminum alloy sheet and the electrolyte were used to assemble a zinc ion symmetrical battery according to the steps of Example 1. 2 At a current density of , the zinc surface after battery cycling is preferentially oriented to the (002) plane, and the zinc surface morphology is shown in Figure 2 .

[0075] Example 7

[0076] The synthesis steps of carbon quantum dots are shown in Example 1.

[0077] Electrolyte configuration scheme:

[0078] Weigh 100 mg of synthesized carbon quantum dot powder and dissolve it in 20 mL of acetone; weigh 8.1 g of ZnCl2 powder and dissolve it in 20 mL of deionized water. Add the acetone dispersion of carbon quantum dots into the zinc chloride solution and ultrasonicate for 1 hour. After standing for 1 day, filter to obtain a clear electrolyte.

[0079] Battery assembly and results:

[0080] A zinc-copper alloy sheet and the electrolyte were used to assemble a zinc-ion symmetrical battery according to the steps of Example 1. 2 At a current density of , the zinc surface after battery cycling is preferentially oriented to the (002) plane, and the zinc surface morphology is shown in Figure 2 .

[0081] Example 8

[0082] The synthesis steps of carbon quantum dots are shown in Example 1.

[0083] Electrolyte configuration scheme:

[0084] Weigh 30 mg of synthesized carbon quantum dot powder and dissolve it in 1 mL of benzyl alcohol; weigh 10.8 g of ZnCl2 powder and dissolve it in 40 mL of deionized water. Add the benzyl alcohol dispersion of carbon quantum dots into the zinc chloride solution and ultrasonicate for 1 hour, let it stand for 1 day, and then filter to obtain a clear electrolyte.

[0085] Battery assembly and results:

[0086] A zinc-copper alloy sheet and the electrolyte were used to assemble a zinc-ion symmetrical battery according to the steps of Example 1. 2 At a current density of , the zinc surface after battery cycling is preferentially oriented to the (002) plane, and the zinc surface morphology is shown in Figure 2 .

[0087] Comparative Example 1

[0088] Weigh 115.0 g ZnSO4·7H2O powder and dissolve it in an appropriate amount of ultrapure water to prepare a 2M ZnSO4 solution. Use commercial zinc foil and 2M ZnSO4 solution to assemble a zinc ion symmetrical battery according to the steps of Example 1, connect it to an electrochemical charge and discharge instrument, and set it to 0.5 mA / cm 2 The cycle current density and the charge-discharge cycle of 1h. After 80h of cycling, the battery failed due to the triggering of voltage protection circuit breaker. The surface dendrites of the zinc foil after cycling were obvious, and the surface morphology was shown in the figure. Figure 5 The zinc foil after recycling contains a lot of byproducts. The crystal plane orientation of zinc is consistent with the (101) orientation of the initial zinc foil. The X-ray diffraction (XRD) spectrum of the recycled zinc foil is shown in Figure 6 Comparative Example 2

[0089] Weigh 54.5M ZnCl2 powder and dissolve it in an appropriate amount of ultrapure water to prepare a 2M ZnCl2 solution. Use commercial zinc foil and 2M ZnCl2 solution to assemble a zinc ion symmetrical battery according to the steps of Example 1, connect it to an electrochemical charge and discharge instrument, and set it to 0.5 mA / cm 2 The cycling current density and the charge-discharge cycle of 15 min. After 40 h of cycling, the battery failed due to the voltage protection circuit breaker. The zinc foil after cycling showed similar dendrite morphology and (101) orientation as those in Comparative Example 1.

[0090] Comparative Example 3

[0091] Synthesis of Hydrophilic Carbon Quantum Dots:

[0092] 9 g of citric acid powder and 3 mL of ethylenediamine were dissolved in 30 mL of deionized water, stirred for 30 min, transferred to a reactor, and heated in an oven at 180° C. for 5 h. After cooling to room temperature, the mixture was freeze-dried to obtain hydrophilic carbon quantum dot powder.

[0093] Electrolyte configuration:

[0094] 11.5 g ZnSO4·7H2O powder was dissolved in 20 mL deionized water to obtain a 2 M zinc sulfate solution. 20 mg of synthesized hydrophilic quantum dots were directly added to the electrolyte to dissolve and obtain a clear hydrophilic quantum dot-regulated zinc sulfate electrolyte.

[0095] Battery assembly and its results:

[0096] A zinc ion symmetrical battery was assembled using zinc foil and the electrolyte according to the steps of Example 1. 2 The battery was short-circuited for 100 h at a current density of 1.5 %. After the battery was cycled, the zinc surface was preferentially oriented to the (101) plane and there were more surface byproducts. The XRD results show Figure 8 The zinc surface morphology is shown in Figure 7 .

[0097] Comparative Example 4

[0098] The synthesis of hydrophilic quantum dots is shown in Comparative Example 3

[0099] Electrolyte configuration:

[0100] 5.4 g ZnCl2 powder was dissolved in 20 mL deionized water to obtain a 2 M zinc chloride solution. 20 mg of the synthesized hydrophilic quantum dots were directly added to the electrolyte to dissolve and obtain a clear hydrophilic quantum dot-regulated zinc chloride electrolyte.

[0101] Battery assembly and its results:

[0102] A zinc ion symmetrical battery was assembled using zinc foil and the electrolyte according to the steps of Example 1. 2 The zinc foil after cycling for 50 h showed a dendrite morphology and (101) orientation similar to those in Comparative Example 3.

Claims

1. An electrolyte containing carbon quantum dots for protecting a zinc negative electrode in a zinc ion battery, characterized in that: The hydrophobic carbon quantum dots are used as electrolyte additives, the electrolyte is a mixture of water and an organic solvent, and the solute is zinc salt; the organic solvent is one or more of methanol, ethanol, isopropanol, acetone, and dimethylformamide.

2. The electrolyte according to claim 1, characterized in that: The volume ratio of the organic solvent to water is greater than 0 and less than or equal to 1.

3. The electrolyte according to claim 1, characterized in that: The solute zinc salt structural formula is ZnX a , where X = Cl - 、SO4 2- 、NO3 - 、CH3COO - CF3SO3 - 、ClO4 - One or more of, a = 1 to 2; the zinc salt ZnX a The concentration is 0.1~5M.

4. The method for preparing the electrolyte according to claim 1, wherein: The steps include: (1) The hydrophobic carbon quantum dot powder is dissolved in a certain amount of organic solvent, wherein the organic solvent is one or more of methanol, ethanol, benzyl alcohol, phenol, propanol, benzene, isopropanol, acetonitrile, propionitrile, isopropionitrile, formaldehyde, acetaldehyde, propionaldehyde, acetone, butanone, formic acid, acetic acid, dimethylformamide, and dimethylformamide, and the concentration of the carbon quantum dots is 0 to 50 mg / mL, and is not 0; (2) Add a certain amount of zinc salt ZnX a Dissolved in aqueous solution, where X = Cl - 、SO4 2- 、NO3 - 、CH3COO - CF3SO3 - 、ClO4 - One or more of, a = 1 to 2; the zinc salt ZnX a Concentration is 0.1~6M; (3) adding the organic dispersion of carbon quantum dots in step (1) to the electrolyte in step (2), stirring until a transparent and clear liquid is obtained, and ultrasonicating for 10 to 500 minutes; (4) The liquid obtained in step (3) is allowed to stand for 0 to 5 days and is not zero, and is filtered to obtain a clarified electrolyte.

5. A zinc ion battery, characterized in that: Contains the electrolyte according to any one of claims 1 to 3, with zinc-based material as the zinc negative electrode active material.

6. The zinc ion battery according to claim 5, characterized in that: The zinc negative electrode is a zinc sheet, zinc foil, zinc powder, zinc mesh, porous zinc or zinc alloy.

Citation Information

Patent Citations

  • Method for preparing carbon quantum dot by carbonizing ketone under alkaline condition

    CN104528684A

  • Preparation method and application of functional carbon quantum dot modified Ag-In-Zn-S quantum dots

    CN112774694A

  • Carbon-dot-regulated metal selenide / carbon composite material regulated as well as preparation method and application of carbon-dot-regulated metal selenide / carbon composite material

    CN113571698A

  • Zinc ion battery electrolyte containing carbon dots as well as preparation method and application of zinc ion battery electrolyte

    CN115911592A

  • Aqueous zinc ion battery and method for protecting zinc negative electrode thereof

    CN116454420A